Einsatzbarrieren fuer Produktkonfiguratoren in der Automatisierungstechnik - Ergebnisse einer empirischen Untersuchung - Szydlowski, M.; Greve-Ecker, I.; Trier, Matthias (Industrie Management Journal 1/2003)

Anforderungen an die IT-Unterstuetzung für Communities of Practice im Unternehmen (in German) - Trier, Matthias (Industrie Management Journal)

Der 'Short-Clip' als Ansatz zur Produktion von video-basiertem E-Learning Content bei der VGU (in German) - Trier, Matthias; Herzog, Michael; Krallmann, Hermann (Proceedings Wirtschaftsinformatik 2003)

Integrating Communities of Practice with e-learning platforms to improve on-the-job-learning - Trier, Matthias (Proceedings of Organizational Knowledge, Learning and Capabilities Conference OKLC 2003, Barcelona, 13. April 2003.)
In knowledge intense business processes, a complex and dynamic body of knowledge is being built bottom-up by experience learning during exception handling and problem solving. Traditional qualification programs do not very effectively provide the special skills required. Communities of Practice are better supporting this dynamic on-the-job learning across hierarchies. Still, CoP approaches and platforms in many organisations can be improved by enriching them with e-learning components to create a connection between the unstructured personalisation strategy of CoPs and the structured training materials. Similarly, e-learning benefits from being linked to communities. In the article, the connections of both areas are analysed to derive a framework for integration. It proposes an agenda of activities for the two domains people-oriented and content-oriented integration of community management and e- learning. These two aspects affect the handling, configuration and design of software features. In a first stage, the challenge is mainly a management and organisational task. Consecutively, the integration processes can be further assessed in order to identify potentials for IT-automatisation.

IT-unterstuetztes Management virtueller Communities of Practice (in German) - Trier, Matthias (Proceedings DoIT Congress 2003, 24.11.2003)

Die Besteuerung von Beteiligungsveräußerungen und Rechtsformneutralität - Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Bidding for envy-freeness: A procedural approach to n-player fair-division problems - Haake, Claus-Jochen; Raith, Matthias; Su, Francis Edward (Social Choice and Welfare)
We develop a procedure for implementing an efficient and envy-free allocation of m objects among n individuals with the possibility of monetary side-payments,assuming that players have quasi–linear utility functions. The procedure eliminates envy by compensating envious players. It is fully descriptive and says explicitly which compensations should be made,and in what order. Moreover,it is simple enough to be carried out without computer support. We formally characterize the properties of the procedure,show how it establishes envy-freeness with minimal resources,and demonstrate its application to a wide class of fair-division problems.

Das Lebensarbeitszeitkonzept als Alternative zur Mehrarbeitszeitzuschlagslösung - Betz, Stefan (Zeitschrift für Planung)

Kontrollsystem - Betz, Stefan (Handwörterbuch Unternehmensrechnung und Controlling)

Catching‐Up, Falling Behind and the Role of FDI:A Model of Endogenous Growth and Development - Gries, Thomas (South African Journal of Economics)

Sophistication Banking als erfolgreiche Strategie im Informationszeitalter - Buhl, H. U.; Kundisch, Dennis; Steck, W. (Zeitschrift für Betriebswirtschaft)

Beratungsqualität von Finanzdienstleistern am Beispiel von Online-Immobilienfinanzierungen mit KFW Darlehen - Kundisch, Dennis (E-Commerce: Netze, Märkte, Technologien)

Trust and Switching Costs in the Financial Services Industry - Kundisch, Dennis; Steck, W. (Recent Advances in Computers, Computing and Communications)

Building Trust - The Most Important CRM Strategy? - Kundisch, Dennis (3rd World Congress on the Management of Electronic Commerce)

Internationale Vergleichsuntersuchung schreckt auf: Deutsches Personalmanagement offenbar nicht immer Spitze - Weber, W; Kabst, Rüdiger

IT-Fachkräfte: Unternehmensbedarf und Qualifizierungsprofile - Eine empirische Studie in deutschen und europäischen Unternehmen, Paderborn 2002 - Weber, W; Kabst, Rüdiger; Habich, J

SEMIFAR models—a semiparametric approach to modelling trends, long-range dependence and nonstationarity - Beran, Jan; Feng, Yuanhua (Computational Statistics & Data Analysis)

Iterative Plug-In Algorithms for SEMIFAR Models—Definition, Convergence, and Asymptotic Properties - Beran, Jan; Feng, Yuanhua (Journal of Computational and Graphical Statistics)

Data-driven decomposition of seasonal time series - Heiler, Siegfried; Feng, Yuanhua (Journal of Statistical Planning and Inference)

On robust local polynomial estimation with long-memory errors - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita; Sibbertsen, Philipp (International Journal of Forecasting)